Surface acoustic wave enabled pipette on a chip. Issue 3 (20th December 2016) - Sesen, Muhsincan; Devendran, Citsabehsan; Malikides, Sean; Alan, Tuncay; Neild, Adrian
Abstract : Presented here is an automated microfluidic platform, pipette on a chip, capable of selectively pipetting subsamples from mobile droplets in the picoliter range with high accuracy using a non-contact approach. The system utilizes acoustic forces, is modular and robust allowing integration with existing lab on a chip devices. Abstract : Mono-disperse droplet formation in microfluidic devices allows the rapid production of thousands of identical droplets and has enabled a wide range of chemical and biological studies through repeat tests performed at pico-to-nanoliter volume samples. However, it is exactly this efficiency of production which has hindered the ability to carefully control the location and quantity of the distribution of various samples on a chip – the key requirement for replicating micro well plate based high throughput screening in vastly reduced volumetric scales. To address this need, here, we present a programmable microfluidic chip capable of pipetting samples from mobile droplets with high accuracy using a non-contact approach. Pipette on a chip (PoaCH) system selectively ejects (pipettes) part of a droplet into a customizable reaction chamber using surface acoustic waves (SAWs). Droplet pipetting is shown to range from as low as 150 pL up to 850 pL with precision down to tens of picoliters. PoaCH offers ease of integration with existing lab on a chip systems as well as a robust and contamination-free droplet manipulation technique in closed microchannels enabling potential implementation in screening and other studies.